Nursing in the health sistematic attention to the families of people with - Maria Salete Bessa Jorge; Consuelo Helena Aires de Freitas; Priscilla Mesquita Luz; Laura Martins Mendes Cavaleiro; Rachel Franklin da Costa (Rev Rene)
The study analysis the scientific production of nursing performance in systematic attention to families of people with mental breakdown through scientific periodic index and published in university libraries, in the MEDLINE, LILACS and SCIELO data bank system within the period of 2000 to 2005. The research has bibliographic nature based upon the assumptions of Pimentel’s analysis, who considers the Raising of material, content analysis with the elaboration of the themes searching to make counter-points among the several authors. The results shown the increasing number of researches that approach the participation of the family in the therapeutic care of people with severe mental breakdown, emphasize conducts and perceptions of families and of professionals about the treatment, and call the attention to the promotion of the social insertion of the family, understanding of needs and promotion of participation of the family in health problems.